Helium isotopes in gases of mineral waters in the Western Caucasus. - Polyak, Boris G; Lavrushin, VYu; Inguaggiato, S; Kikvadze, O E (PANGAEA, 2011)
Helium isotope composition as an indicator of the mantle-derived component was studied in gases from mineral springs, stratal waters, and mud volcanoes developed west of the Teberda River valley (10 objects) and two springs in the central segment of the Greater Caucasus orogen between the active El'brus and Kazbek volcanoes. In the western segment of the orogen ratios of 3He/4He = R_corr vary from 46x10**-8 to 114x10**-8 (from 0.33 to 0.81 R_atm, where R_atm = 1.4x10**-6 is the atmospheric ratio). They are substantially lower relative to ratios in the vicinity of El'brus and Kazbek and close to those in samples from the central segment (from 70x10**-8 to 134x10**-8 (from 0.50 to 0.96 R_atm), as well as to ratios previously recorded in the Caucasian Mineral Waters (CMW) area. Moreover, concentration of 3He in them is notably higher than its crustal radiogenic level characteristic of mud volcanoes in the Taman Peninsula, where 3He/4He varies from 1.4x10**-8 to 2.8x10**-8 (from 0.01 to 0.02 R_atm). Nitrogen-methane gas from northern piedmonts of the western Caucasus also contains nonatmogenic components including radiogenic 40Ar (40Ar/36Ar = 900), excessive nitrogen (~87% of total N2 concentration in sample) and mantle He. These data specify distribution of mantle derivates along the orogen strike and age of intrusive magmatic activity in its different segments.
Main components and isotopic composition of gases from mineral waters of the Taman Peninsula and Caucasus
Keywords: Archive of Ocean Data; ARCOD